Childhood maltreatment, depression and their link to adult economic burdens - Petersen, Julia; Schulz, Ann-Christin; Brähler, Elmar; Sachser, Cedric; Fegert, Jörg M.; Beutel, Manfred E. (Frontiers in Psychiatry, 2022)
Background: Adult depression is a common consequence of adverse childhood experiences. There is also a higher likelihood of being affected by economic burdens. As depression has been associated with economic burden, these long-term sequelae of childhood adversity are likely to interact. Goals: We investigated depression and economic consequences, such as unemployment, lower level of education, lower income as long-term sequelae of adverse childhood experiences in adulthood and their interaction. Methods: Childhood Maltreatment was measured by the German version of the Adverse Childhood Experience (ACE) questionnaire. Depression was measured by the Patient Health Questionnaire (PHQ-2). Latent class analysis was used to examine co-occurrences of ACEs. Binary logistic regressions were applied to investigate the risks of suffering economic burdens, with depression as a mediator. Results: Depressive symptoms increased with the number of ACEs and were highest in those reporting four or more, especially amongst those who experienced sexual and emotional abuse, as well as neglect. Mediation analysis shows a significant mediation effect of depression on almost all economic burdens. Migration background and gender also play a key role. Conclusion: The mediation effect increased the already heightened negative impact that having been exposed to multiple ACEs had on economic life in adulthood. The strong association between (multiple) ACEs, depression and unemployment needs to be further investigated.